A study of the stress distributions necessary to maintain rubber in a state of torsion - Hall, M. M. (College of Aeronautics, 1968)
Quantitative measurements have been made of the time dependent normal stress distributions and torques which are necessary to maintain a state of torsion in: (i) a solid right circular cylinder of rubber, (ii) rubber contained between a cone and touching flat plate. The measurements on the solid rubber cylinder, under quasi-elastic conditions cannot be described by the kinetic theory of elasticity. There are considerable experimental difficulties involved in measurements on the cone and plate system but these results also suggest an inadequacy in the ability of the kinetic theory to describe finite deformations in rubbers.